(untitled) (Journal of actual problems of jurisprudence, 2019)
There are some problems of providing of environmental safety in this article of is considered. This article discusses some of the legal issues of environmental security. Environmental safety of any geographically organized society, including Kazakhstan, associated with internal and external factors. Environmental Safety RK promotes the prevention and mitigation of internal environmental threats arising from the dominance of economic interests over environmental and external threats caused in connection with the implementation of the national interests of other countries. Along with other factors, prevention of threats and dangers of environmental safety considerable space is devoted to the legal framework for environmentally sustainable development. Keywords: environment, environmental safety, environmental issue.